2003
DOI: 10.1097/00009957-200309000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The effects of limb lengthening on growth

Abstract: The purpose of this study was to determine the effects of limb lengthening on the rate of growth of the lengthened limb. The rate of growth of the lengthened and control (contralateral) limb segment were determined radiographically pre- and postoperatively in 19 skeletally immature patients (20 limbs). There were 13 femoral and seven tibial lengthenings. The mean age at the time of lengthening was 9.4 years (range 4.2-12.3). The limbs were lengthened by a mean of 6.7 cm (24%). Mean follow-up was 3.6 years. No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The stimulatory effect when lengthening was performed under optimal conditions was found to reach up to 5% of the final lengthened segment. Some authors have found no change in growth rate in older patients [17,21,24,46], although some authors have found stimulatory effects in young patients despite a higher mean percent lengthening [38]. In our study, using preoperative and postoperative measurements of developmental femoral and overall length discrepancies matched the findings of Popkov et al and others, showing no detrimental effect on femoral growth in young patients who underwent a relative femoral lengthening greater than 23.5% [17,21,45].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The stimulatory effect when lengthening was performed under optimal conditions was found to reach up to 5% of the final lengthened segment. Some authors have found no change in growth rate in older patients [17,21,24,46], although some authors have found stimulatory effects in young patients despite a higher mean percent lengthening [38]. In our study, using preoperative and postoperative measurements of developmental femoral and overall length discrepancies matched the findings of Popkov et al and others, showing no detrimental effect on femoral growth in young patients who underwent a relative femoral lengthening greater than 23.5% [17,21,45].…”
Section: Discussionsupporting
confidence: 84%
“…Some authors have found no change in growth rate in older patients [17,21,24,46], although some authors have found stimulatory effects in young patients despite a higher mean percent lengthening [38]. In our study, using preoperative and postoperative measurements of developmental femoral and overall length discrepancies matched the findings of Popkov et al and others, showing no detrimental effect on femoral growth in young patients who underwent a relative femoral lengthening greater than 23.5% [17,21,45]. However, our study could not support the hypothesis that femoral lengthening stimulates growth as has been previously postulated [34,38].…”
Section: Discussionmentioning
confidence: 99%
“…So, the calculated average change of 4% in our children means between 8 and 20 mm. If we take into account that lengthening in many cases causes further growth retardation (Sharma et al 1996, Viehweger et al 1998, Sabharwal et al 2000, McCarthy et al 2003), we have observed a remarkable effect.…”
Section: Discussionmentioning
confidence: 80%
“…Growth stimulation has been reported in a limited number of patients after femoral lengthening in 2 studies (Shapiro 1987, Sabharwal et al 2000). Group effects have not been reported (Shapiro 1987, Hope et al 1994, Sabharwal et al 2000, McCarthy et al 2003). It is known that after a femoral fracture, growth in the length of the traumatized leg may increase temporarily, but this effect always lasts less than 2 years after the trauma (De Sanctis et al 1996, Stephens et al 1989).…”
Section: Discussionmentioning
confidence: 98%
“…Growth rate (GR) was determined from the ratio of the difference of the actual length of the tibia (ALT) of 2 successive radiographs divided by the time span in years (McCarthy et al 2003): GR = (ALT current – ALT previous) / time span in years.…”
Section: Methodsmentioning
confidence: 99%